The Evolution of Collective Behavior: A Dramaturgical Presentation - Rodger A. Bates (Journal of Public and Professional Sociology)
The evolution of collective behavior is examined through a dramaturgical presentation in the form of the minutes of faculty meeting between Plato, Skinner and a number of sociologists. The strengths and weaknesses of a number of traditional perspectives are illustrated along with the emergence new forms of collective behavior in the 21st century.